Chromium valence change in trivalent chromium conversion coatings on aluminium deposited under applied potentials. (1st May 2020) - Qi, Jiantao; Światowska, Jolanta; Skeldon, Peter; Marcus, Philippe
Abstract: The electroassisted (EA) deposition of trivalent chromium conversion coatings on aluminium is investigated with a focus on the influence of applied potential on the chromium valence state, as determined by Raman spectroscopy. The morphology and compositions of the coatings were investigated by scanning electron microscopy and energy-dispersive spectroscopy. The EA coatings were formed in naturally-oxygenated SurTec 650 chromitAl solution at constant potentials of −1.5 and −0.5 VSCE . The coatings contained chromium and zirconium constituents. The potentials resulted in net cathodic and anodic current densities, respectively, during the coating growth. Comparisons were made with coating formation at the open-circuit potential (OCP). The coating thickness increased in order −0.5 VSCE < OCP < −1.5 VSCE, a result of increasing alkalinity from the cathodic reaction that facilitates deposition of the coating constituents. Fresh coatings formed at −1.5 VSCE revealed the presence of Cr 6+ species. By contrast, Cr 6+ species were not resolved in the coating formed at −0.5 VSCE . It is proposed that less H2 O2 is generated at −0.5 VSCE to oxidize Cr 3+ coating species.